Reduced day-to-day variation accompanies adaptive plasticity in the primate spinal stretch reflex. - Jonathan Wolpaw; O'Keefe, J. A.; Kieffer, V. A.; Sanders, M. G. (Neuroscience letters, 1985)
Monkeys can change the amplitude of the spinal stretch reflex (SSR), or M1, when reward is made contingent on amplitude. The present study demonstrates that reduced SSR day-to-day variation accompanies such adaptive SSR change. This finding supports the assumption that initial, phase I, SSR change results from contingency-appropriate stabilization of tonic activity in relevant descending spinal cord pathways.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex

Adaptive plasticity in the spinal stretch reflex. - Jonathan Wolpaw; Kieffer, V. A.; Seegal, R. F.; Braitman, D. J.; Sanders, M. G. (Brain research, 1983)
Monkeys can change the amplitude of the spinal stretch reflex without change in initial alpha motor neuron tone, as measured by EMG, or in initial muscle length. Change is apparent in 5-10 days, continues to develop over weeks, and persists during inactive periods. Spinal stretch reflex change may be a valuable system for studying the neuronal and synaptic bases of an adaptive change in primate CNS function.
Keywords: Learning; Memory; plasticity; primate; spinal reflex; stretch reflex